Spatial Heterogeneity of Child Malnutrition and Governance Fragility: A Geographically Weighted Regression Analysis of Stunting and Political Instability in Indonesia’s Peripheral Regions - Fitriyanti Fitriyanti; Aylin Yermekova; Ahmad Erza; Alex Putra Pratama (Open Access Indonesia Journal of Social Sciences, 2025)
Stunting remains a critical public health challenge in Indonesia, particularly in peripheral regions known as Terdepan, Terluar, Tertinggal (3T). While biological and nutritional factors are well-documented, the impact of political instability and governance fragility on health outcomes remains under-explored. This study investigates the spatial relationship between political instability and stunting prevalence across Indonesia's peripheral districts. We employed Geographically Weighted Regression (GWR) to analyze spatial non-stationarity. Data were analyzed for 122 peripheral districts, integrating the Stunting Prevalence Index (SPI) as the dependent variable and the Political Instability Index (PII), poverty rates, and healthcare accessibility as predictors. Global Moran’s I was used to detect spatial autocorrelation. Significant spatial clustering was identified (Moran’s I = 0.48, p < 0.001). The GWR model significantly outperformed the Ordinary Least Squares (OLS) model (R-squared GWR = 0.76 versus R-squared OLS = 0.54), revealing that political instability has a disproportionately higher impact on stunting in the Eastern Indonesia cluster—specifically Papua and Maluku—compared to Western peripheral zones. In conclusion, stunting interventions in peripheral regions must transcend clinical nutrition to include governance stabilization. Tailored, location-specific policies are essential for regions where political fragility exacerbates supply chain disruptions for health services.